(untitled) (Journal of Engineering, 2016)
This study aims to assess the accuracy of digital elevation model (DEM) created with utilization of handheld Global Positioning System (GPS) and comparing with Advanced Spaceborne Thermal Emission and Reflection Radiometer Global Digital Elevation Model (ASTER GDEM), version 2. It is known that the quality of the DEM is affected by both of accuracy of elevation at each pixel (absolute accuracy) and accuracy of presented morphology (relative accuracy). The University of Baghdad, Al Jadriya campus was selected as a study area to create and analysis the resulting DEM. Additionally, Geographic Information System (GIS) was used to visualize, analyses and interpolate GPS track points (elevation data) of the study area. In this research, three additional DEMs were created using 60%, 30% and 15% of the all GPS track points to deduce the effect of the number of the included points on the accuracy of the resulting DEM. The study findings show a high resolution for the resulting DEM less than 5m when taking into consideration all GPS tracking points that observed in this research. Moreover, the resulting DEM has relative accuracy better than absolute accuracy and reaches to around 2m. By comparing with ground control points (reference points), the quality of handheld GPS DEM shows considerable improvement better than ASTER GDEM. Thus, this study indicates to improve the accuracy level of handheld GPS DEM by about 40% with increasing the observed number of GPS track points to twice.